The red ledger. Volume 2, parts 4 -5 -6 : recall - Wild, Meredith (Waterhouse Press, 2018)
The second I spared Isabel's life, everything changed. I used to deal in death wishes. Now the instinct to protect her charts the course. Because every time I turn away from her, something turns me back. She's uncovered a side of me that I can no longer ignore. Doesn't change the fact that she doesn't belong in my world. Isabel's learning to hold her own, but nothing can prepare her for the life I'm being called back into. With a long road ahead of us, I won't make promises I can't keep. She can barely accept the dark deeds of my past--a bloody history spelled out in a ledger she's more preoccupied with than I'd like. When an old associate sets a dangerous plan in motion, I can't hide who I really am. And there's no turning back...